Thermochemical Analysis of Hypergolic Propellants Based on Triethylaluminum/Nitrous Oxide - Stephen M. Davis; Nadir Yilmaz (International Journal of Aerospace Engineering)
The vacuum specific impulse, density vacuum specific impulse, and solid exhaust products were examined for several propellant formulations based on the pyrophoric material triethylaluminum (TEA) using CEA thermodynamics code. Evaluation of TEA neat and mixed with hydrocarbon fuels with LOX, N2O, N2O4, liquefied air, and HNO3 were performed at stoichiometry. The vacuum specific impulse of neat TEA with N2O is comparable to that of nitric acid with the same, but the N2O formulation will produce slightly less solid products during combustion. Additionally, N2O-TEA propellants have vacuum specific impulses and density vacuum specific impulses within 92.9% and 86.7% of traditional hydrazine propellant formulations under stoichiometric conditions.